Perceptions of social and work functioning are related to social anxiety and executive function in autistic adults. (October 2021) - Woolard, Alix; Stratton, Elizabeth; Demetriou, Eleni A; Boulton, Kelsie A; Pellicano, Elizabeth; Glozier, Nick; Gibbs, Vicki; Rogerson, Nicole; Quinn, Philippa; Hickie, Ian B; Guastella, Adam J
Autistic adults report concerns with social skills and unemployment. Despite anxiety and difficulty with executive cognitive skills being associated with autism, no studies to date have investigated relationships between anxiety or executive cognition with social and work functioning. This study aimed to investigate the associations between perceived social anxiety, perceived and objective executive function, and perceived social and work functioning in a sample of autistic people. A total of 62 participants completed self-report questionnaires of social anxiety (via the Liebowitz Social Anxiety Scale), mental health (via the Depression Anxiety Stress Scale), executive cognition (via the Behaviour Rating Inventory of Executive Function) and perceived social and work functioning (the Work and Social Adjustment Scale), and a smaller subset ( n = 36–40) completed performance-based executive function tasks (Trail Making Task and Rapid Visual Processing Task). Participants who reported having more social anxiety and more difficulty with executive cognition also perceived themselves as having poorer social and work functioning. Performance-based executive function was not related to social or work functioning. Our results suggest that perceived social anxiety and executive cognition are both areas that have potential to be targeted to investigate whether they improve social and vocational outcomes for autistic people. Lay abstract: Many autistic adults have trouble in social situations and at work. Researchers do not know exactly why autistic people might find it difficult in these environments, and no studies to date have looked the way anxiety or other cognitive processes might affect autistic peoples' ability to socialise and succeed in getting and keeping jobs. Anxiety (how much you worry) and difficulty with getting stuff done or switching attention (known as executive function) can be concerns for autistic people and may contribute to social and work difficulties. This study looked at the relationships between the way autistic people perceived their anxiety and executive functioning and their ability to socialise and work. Sixty-two autistic participants completed questionnaires related to their ability to socialise and work, their social anxiety and their executive function. We found that participants who thought that they had poorer ability to work also found themselves to have more difficulties with executive function and they were more socially anxious. Our results showed that how autistic participants perceived their social anxiety and executive function were important in their perception of their social skills and work ability. This study supports the idea that anxiety and executive function could be targeted in interventions to support autistic people and their social and work outcomes.